Acetylcholinesterase is not a generic marker of extracellular vesicles. Issue 1 (3rd July 2019) - Liao, Zhaohao; Jaular, Lorena Martin; Soueidi, Estelle; Jouve, Mabel; Muth, Dillon C.; Schøyen, Tine H.; Seale, Tessa; Haughey, Norman J.; Ostrowski, Matias; Théry, Clotilde; Witwer, Kenneth W.
ABSTRACT: Acetylcholinesterase (AChE) activity is found in abundance in reticulocytes and neurons and was developed as a marker of reticulocyte EVs in the 1970s. Easily, quickly, and cheaply assayed, AChE activity has more recently been proposed as a generic marker for small extracellular vesicles (sEV) or exosomes, and as a negative marker of HIV‐1 virions. To evaluate these proposed uses of AChE activity, we examined data from different EV and virus isolation methods using T‐lymphocytic (H9, PM1 and Jurkat) and promonocytic (U937) cell lines grown in culture conditions that differed by serum content. When EVs were isolated by differential ultracentrifugation, no correlation between AChE activity and particle count was observed. AChE activity was detected in non‐conditioned medium when serum was added, and most of this activity resided in soluble fractions and could not be pelleted by centrifugation. The serum‐derived pelletable AChE protein was not completely eliminated from culture medium by overnight ultracentrifugation; however, a serum "extra‐depletion" protocol, in which a portion of the supernatant was left undisturbed during harvesting, achieved near‐complete depletion. In conditioned medium also, only small percentages of AChE activity could be pelleted together with particles. Furthermore, no consistent enrichment of AChE activity in sEV fractions was observed. Little if any AChE activity is produced by the cells we examined, and this activity was mainly present in non‐vesicular structures, as shown by electron microscopy. Size‐exclusion chromatography and iodixanol gradient separation showed that AChE activity overlaps only minimally with EV‐enriched fractions. AChE activity likely betrays exposure to blood products and not EV abundance, echoing the MISEV 2014 and 2018 guidelines and other publications. Additional experiments may be merited to validate these results for other cell types and biological fluids other than blood.